The effect of variations in electric load on the performance of a 3 kW Micro Hydro Power Plant using an undershot waterwheel - Yusuf Dewantoro Herlambang; Bono Bono; Gatot Suwoto; Suwarti Suwarti; Baktiyar Mei Hermawan; F Gatot Sumarno; Margana Margana; Marliyati Marliyati (Politeknik Negeri Lhokseumawe, 2023)
The purpose of this study is to evaluate the performance of the undershot water wheel type with a 3 kW generator as a micro-hydro power plant that generates electricity by utilizing water power from paddy fields and local resources. Where the irrigation canal can irrigate approximately 247 hectares of rice fields during the dry season. The research technique employs a waterwheel with a 1.1-meter diameter, 12 blades with a 70-centimeter blade arm length, and a 2-inch shaft diameter. The transmission system employs a chain to increase rotation and decrease slippage and rotation losses, making it simpler to drive the generator to produce electricity. The test was conducted by varying the lamp capacity from 100 W to 800 W while maintaining constant water discharge and flow. Water discharge, water head, generator rotation, electric current traveling through the load, and output voltage are the test parameters. With a discharge of 0.476 m3/s, a water flow speed of 3.229 m/s, a waterwheel rotation of 42.39 rpm, and electric power of 207 W, the utmost efficiency value of 8.35% was determined.